Case Report: Extracorporeal photopheresis for cutaneous lupus erythematosus induces putatively atheroprotective B and T cell responses - Visentini, Marcella; Ozsvar-Kozma, Maria; Pacella, Ilenia; Pinzon Grimaldos, Alessandra; Falco, Federica; Shafii-Bafti, Mahnaz; Minicocci, Ilenia; La Gualana, Francesca; Carlesimo, Maurizio; Casato, Milvia; Basili, Stefania; Arca, Marcello; et al. (Frontiers in Immunology, 2026)
Extracorporeal photopheresis (ECP) involves the reinfusion of autologous peripheral blood lymphocytes rendered apoptotic by in vitro exposure to psoralen and ultraviolet A light. Antigenic determinants presented by apoptotic lymphocytes, primarily T cells, elicit immunomodulatory responses that have shown therapeutic benefit in several conditions, including cutaneous T-cell lymphoma, graft-versus-host disease, and various inflammatory/autoimmune disorders. We treated with ECP a 41-year-old woman diagnosed with cutaneous lupus erythematosus and concomitant hypercholesterolemia, achieving a marked improvement of skin lesions. A study in hypercholesterolemic apolipoprotein E-deficient mice demonstrated that immunization with syngeneic apoptotic thymocytes, a process mimicking ECP, induced the production of IgM antibodies against oxidized low-density lipoproteins (OxLDL) that attenuated atherosclerosis. Thus, we explored whether ECP could similarly induce anti-OxLDL antibodies in our patient. Indeed, over the course of a 14-week ECP treatment we observed a steady increase in circulating IgM antibodies against malondialdehyde-modified LDL, a class of antibodies known to confer atheroprotection in preclinical models. Additionally, we documented an increase in circulating regulatory T cells, which are recognized as suppressing pro-atherogenic immune responses. These findings support the translational potential of a preclinical atheroprotection model and provide a proof of concept for clinical trials evaluating ECP in autoimmune diseases associated with accelerated atherosclerosis, where achieving dual benefits, clinical improvement and reduced cardiovascular risk, may be feasible.